PENGARUH KERAGAMAN MAKANAN TERHADAP STUNTING PADA BALITA YANG BERADA DI WILAYAH KERJA PUSKESMAS KALUMPANG, KOTA TERNATE - Nofiandri Mochtar; Nur Muhammad Ali (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Globally malnutrition is still a major problem in toddlers. Malnutrition from the fetus to a two-year-old child will affect cognitive development and also affect physical development, as well as intelligence and mental agility, which also affects work productivity. The nutritional problem that has not been resolved and is still a major problem today is the problem of stunting toddlers in Indonesia. This study aims to determine the effect of diet on stunting in toddlers. This research is an analytical survey research with a cross-sectional design. This research was conducted from September to November two thousand and twenty-two at the Kalumpang Ternate Public Health Center. The population in this study were toddlers who were stunted in the working area of ​​the Kalumpang Health Center. Sampling in this study is the total technique or census sampling. As many as thirty respondents for the sample size in this study. Data were analyzed using a computer program and presented in tabular and narrative form. Data analysis was performed using multivariate and univariate methods. Bivariate analysis was used to determine the correlation between the dependent variable and the independent variable. Meanwhile, multivariate analysis was used to determine the O.R (Odd Ratio) value. The multivariate analysis used is logistic regression. The results obtained are the more diverse types of food consumed by toddlers, the less likely children are to experience stunting. Food diversity influences the incidence of stunting in toddlers in the working area of ​​the Kalumpang Health Center, Ternate City.